2021
DOI: 10.1007/s11302-021-09797-4
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CD73 increases exercise power in mice

Abstract: Ecto-5′-nucleotidase or CD73 is the main source of extracellular adenosine involved in the activation of adenosine A 2A receptors, responsible for the ergogenic effects of caffeine. We now investigated the role of CD73 in exercise by comparing female wild-type (WT) and CD73 knockout (KO) mice in a treadmill-graded test to evaluate running power, oxygen uptake (V̇O 2 ), and respiratory exchange ratio (RER) — the gold standards characterizing physical performance. Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
6
10
0
Order By: Relevance
“…Our results strengthen the hypothesis about the ergogenic mechanism of caffeine through adenosinergic antagonism in the central nervous system [7][8][9]16]. Mice treated with caffeine and SCH 58261 demonstrated increased running performance, while caffeine-treated forebrain A 2A R knockouts did not demonstrate this effect [16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results strengthen the hypothesis about the ergogenic mechanism of caffeine through adenosinergic antagonism in the central nervous system [7][8][9]16]. Mice treated with caffeine and SCH 58261 demonstrated increased running performance, while caffeine-treated forebrain A 2A R knockouts did not demonstrate this effect [16].…”
Section: Discussionsupporting
confidence: 86%
“…Davis first demonstrated that adenosine agonist 5′-N-ethylcarboxamide adenosine (NECA) injected into the rat ventricles increases running performance [7]. We then demonstrate the role of extracellular adenosine in the development of fatigue in mice [8] and the pivotal role of neuronal A 2A R in the mouse forebrain for the ergogenic effects of caffeine [1, 9]. On the other hand, the increase in A 2A R [10, 11] is a hypothetical mechanism for the fatigue symptom in neurological diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…We previously described that mice injected with AOPCP display a similar pattern of spontaneous locomotion in the open field compared to control mice [ 24 ] as well as a similar physical performance at low to moderate intensities [ 33 ] and a similar spatial reference memory performance [ 25 ]. The impact of AOPCP, applied intracerebroventricularly, was now tested in fear conditioning memory ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the increased calcium concentrations in the muscle cytoplasm, increases calcium binding opportunities for troponin to expose myosin binding sites and thus enhance skeletal muscle contraction force (Smith, 2003;Hogervorst et al, 2008;Connell et al, 2016;Pires et al, 2018;Saville et al, 2018;Shabir et al, 2018;Franco-Alvarenga et al, 2019;Huertas et al, 2019;Aguiar et al, 2020;Cipollone et al, 2020;Machado et al, 2020;Sanchis et al, 2020;Wang et al, 2020;Lorenzo Calvo et al, 2021;Vázquez et al, 2022;Ágoston et al, 2022). Centrally, the most accepted mechanism of how CAF exerts its effect on cognition is its influence on the central neuronal adenosine receptors, specifically the A 1 and A 2A adenosine receptors (Fredholm et al, 1999;Dunwiddie and Masino, 2001;Smith, 2003;Borycz et al, 2007;Hogervorst et al, 2008;Pandolfo et al, 2013;Connell et al, 2016;Cunha, 2016;Leffa et al, 2018Leffa et al, , 2019Pires et al, 2018;Saville et al, 2018;Shabir et al, 2018;Franco-Alvarenga et al, 2019;Huertas et al, 2019;Lopes et al, 2019;Aguiar et al, 2020Aguiar et al, , 2021Cipollone et al, 2020;Machado et al, 2020;Sanchis et al, 2020;…”
Section: Neurobehavioral Cognitive and Neurophysiological Effects Of ...mentioning
confidence: 99%
“…Centrally, the most accepted mechanism of how CAF exerts its effect on cognition is its influence on the central neuronal adenosine receptors, specifically the A 1 and A 2A adenosine receptors (Fredholm et al, 1999;Dunwiddie and Masino, 2001;Smith, 2003;Borycz et al, 2007;Hogervorst et al, 2008;Pandolfo et al, 2013;Connell et al, 2016;Cunha, 2016;Leffa et al, 2018Leffa et al, , 2019Pires et al, 2018;Saville et al, 2018;Shabir et al, 2018;Franco-Alvarenga et al, 2019;Huertas et al, 2019;Lopes et al, 2019;Aguiar et al, 2020Aguiar et al, , 2021Cipollone et al, 2020;Machado et al, 2020;Sanchis et al, 2020;Wang et al, 2020;Lorenzo Calvo et al, 2021;Vázquez et al, 2022;Ágoston et al, 2022). Extracellular adenosine in the brain is formed by AMP-selective enzymes, such as CD73, and is dependent on the rate of synthesis and breakdown of ATP (Aguiar et al, 2021). CAF is an adenosine antagonist whereby it blocks adenosine binding to A 1 and A 2A receptors by reducing adenosine's ability to inhibit DA activity.…”
Section: Neurobehavioral Cognitive and Neurophysiological Effects Of ...mentioning
confidence: 99%